Operative findings on microsurgical exploration of the cerebello-pontine angle in trigeminal neuralgia. Issue 12 (December 1983) - Richards, P; Shawdon, H; Illingworth, R
Abstract : The anatomical findings in 52 patients undergoing posterior fossa exploration for idiopathic trigeminal neuralgia are described. Anatomical abnormalities in the cerebello-pontine angle were found in 46. The commonest was an arterial loop indenting or distorting the nerve at the root entry zone. In view of this the operative procedure has been changed from root section to microvascular decompression.